Implementação da coleta seletiva de estabelecimentos comerciais por meio de um aplicativo de roteamento de veículos: um estudo de caso no Rio de Janeiro - Franca, Luíza Santana (2017)
According to UNEP and ISWA (2015), the world urban solid waste can grow by 7 to 10 billion tons per year and in Brazil, 52.0% of the total collected destined to landfills in 2014 (SNIS, 2016) and 3.326 municipalities do not have a environmental friendly destination (ABRELPE, 2015). Considering the importance of the waste sector development, the present work aims to economically evaluate the practice of the selective collection of recyclable waste, so that this can be reused and has an alternative final destination. The analysis of this work was done through the use of the software ORTEC Routing and Dispatch (ORD), in order to simulate the operation of the case study in a private company responsible for urban solid waste collection from commercial establishments, which operates in the Metropolitan Region of Rio de Janeiro. The selective collection was planned in 16 scenarios where the recyclable waste separation was gradually increased, considering the population awareness. The results of the simulations show that despite the 41,44% increase in the total mileage covered by the routes when Scenario 16 (all the recyclable waste were collected which could be usable) where compared to Scenario 1 (current base scenario), it is possible to obtain a reduction of 11,39% of the total mileage covered by the selective routes. In this way, a reduction of 27,72% of the total cost was observed, when the new planning was compared to the base scenario.